Efektivitas bahan herbal dengan kandungan antioksidan terhadap potensi perbaikan fisiologis mencit yang diinduksi glukosa: literature review terhadap potensi menjadi bahan fungsional dalam upaya preventif dan terapi pengobatan pasien diabetes mellitus - Bakar, Abu; SSN, R. Moch Satrio (Maliki Interdisciplinary Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia due to indulin secretion dysfunction or insulin resistance. The prevalence of DM continues to increase globally, demanding more innovative therapeutic approaches, including the utilization of herbal ingredients with antioxidant content to prevent serious complications. Purpose: This study aims to evaluate the effectiveness of herbal ingredients with antioxidant content on physiological improvement in glucose-induced mice, and explore their potential as functional ingredients in the prevention and therapy of DM. Methods: This study used a systematic literature review approach using PRISMA and Cochrane Handbook methods. Data were collected from scientific databases such as PubMed, ScienceDirect, and ResearchGate, limited to the last 10 years. The eligibility criteria used the PICO framework and the results were analyzed descriptively. Results: Herbal extracts such as soybean seeds, ginger, rosella flowers, and corn hair showed significant effects in lowering blood glucose levels, improving pancreatic β-cell structure, and increasing insulin sensitivity. The combination of these ingredients produced a stronger synergistic effect than single ingredients. Conclusion: Herbal extracts with antioxidant content have the potential to be an effective and safe functional therapy for DM. Further research is needed to test toxicity and long-term effectiveness to support the development of herbal medicine formulations as an alternative treatment for DM.